The evolution of computerised notational analysis through the example of racket sports - Hughes, M.; Hughes, M. T.; Behan, H. (International Journal of Sports Science and Engineering, 2007)
By analysing past and current work in racket sports, it was found that notational analysis of sport could be systematically analysed by using these delimitations. The development of analysis and technology in the analysis of racket sports The technological developments in notational analysis have inevitably lagged those in the applied computing technology environment. Application of feedback in racket sports The main applied areas of objective feedback were found to be: Tactical evaluation, Technical evaluation, Movement analysis, Databases and modelling, Performance profiling The definition of profiles is much less a matter of guesswork because of methodological advances. Reliability The methods of measuring and calculating the reliability of non-parametric data has grown with research over the last few years. Areas of Research and Support More research in modelling in performance analysis is vital as we extend our knowledge and databases into those exciting areas of prediction. It is clear from these analyses of the on-going research and development work in racket sports, that the working notational analyst must have a broad set of skills and be prepared to maintain and extend those skills just as the research in this area develops the knowledge base.